Trading Butterflies: The Representation of Asian Sex Workers in Vollmann and Houellebecq (ENTHYMEMA, 2019)
The article compares the representation of Asian sex workers in William T. Vollmann’s Butterfly Stories(1993) and Michel Houellebecq’s Platform(Plateforme, 2001). Both the novels are set in South-East Asia, and both involve an apologetic and romanticised description of the sex trade. By comparing the two novels, I argue that both authors’ treatments of the sex industry develop a critique of Western Orientalism, and at the same time sympathy for and complicity with the colonial power dynamics that regulate the relationships between Asian countries and the West.